1989
DOI: 10.1002/ijc.2910440515
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer in women receiving hormone replacement therapy

Abstract: Cancer risk following treatment with non-contraceptive estrogens was studied in a population-based cohort of 23,244 women. Complete follow-up for an average of 6.7 years revealed 1,087 incident cancers versus 962.5 expected (relative risk/RR/ = 1.13; 95% confidence interval 1.10-1.20). We confirmed the recent findings of a more detailed analysis of the same cohort, based on a 1-year shorter follow-up period, namely: a markedly increased risk of endometrial cancer (RR = 1.8; 1.5-2.1), notably in women receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
133
1
5

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(143 citation statements)
references
References 35 publications
4
133
1
5
Order By: Relevance
“…19,22,24,25 Such differences in geographic region, as well as differences in study design and the definition of variables, make the comparison of results difficult. Two studies from East Asia 17,27 indicated that a shorter menstrual cycle is associated with increased lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19,22,24,25 Such differences in geographic region, as well as differences in study design and the definition of variables, make the comparison of results difficult. Two studies from East Asia 17,27 indicated that a shorter menstrual cycle is associated with increased lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies have reported on the association of HRT and risk of lung cancer. 18,19,21,22,[24][25][26]28,30,31,35 Most of these studies do not define whether their results pertain to estrogen alone or estrogen plus progestin. One early cohort study from Sweden, 19 which assessed exposure to both potent estrogens and weaker Each factor is adjusted for all other factors, including for parity (4 levels), age at menarche (4 levels), menopausal status (pre-, peri-and postmenopausal), oral contraceptive use (ever/never), hormone replacement use (ever/never), body mass index (continuous), education (3 categories), smoking status (never, former smoker and current smoker), pack-years of smoking (continuous), study center and randomization group (intervention versus control).-2 Among parous women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The association between HRT use and lung cancer risk is inconsistent. In a Swedish populationbased cohort study, HRT use was associated with an increased lung cancer risk, 20 whereas a study in Japan 21 showed that induced menopause and HRT use were associated with an elevated lung cancer risk compared with normal menopausal women who did not use HRT. A recent Canadian cohort study demonstrated that long-term HRT use is associated with increased risk of lung cancer.…”
mentioning
confidence: 99%